2020
DOI: 10.1021/acs.organomet.0c00078
|View full text |Cite
|
Sign up to set email alerts
|

Ga(N,P) Growth on Si and Decomposition Studies of the N–P Precursor Di-tert-butylaminophosphane (DTBAP)

Abstract: III/V semiconductors containing small amounts of nitrogen (dilute nitrides) are promising for applications such as lasers and solar cells. Metal−organic vapor-phase epitaxy (MOVPE) is a widely used technique for growing III/V semiconductors on an industrial scale, and the growth of dilute nitrides with this method is promising for later successful market entry. The main issues of dilute nitrides are carbon incorporation and low nitrogen incorporation efficiency of the conventional N precursors. Due to the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…[22] Recently, we showed that interpnictogen compounds are useful as precursors for the preparation of doped semiconductors via MOCVD processes. [27][28][29][30][31] Using aryl substituents at bismuth, could give access to interpnictogen compounds that prove useful as precursors.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Recently, we showed that interpnictogen compounds are useful as precursors for the preparation of doped semiconductors via MOCVD processes. [27][28][29][30][31] Using aryl substituents at bismuth, could give access to interpnictogen compounds that prove useful as precursors.…”
Section: Introductionmentioning
confidence: 99%
“…This setup is additionally described in more detail in ref 21 and has already been successfully used for gas-phase analysis of TBAs, a novel N−As precursor ditertiarybutylaminoarsane and the corresponding P analogue ditertiarybutylaminophosphane. 47,48 As mentioned before, only the surface temperature of the susceptor is determined in our setup. Due to the distance of the gas collection point at the nozzle from the susceptor, the effective gas temperature is determined by the correlation of the TBAs decomposition results of ref 21 with data from ref 5.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, due to the FFT-based concept, the measurement time of a single mass spectrum can be lower than 2 s, which makes this setup very suitable for real-time gas-phase analysis, and it should be capable for the detection of impurities within the reactor system. This setup is additionally described in more detail in ref and has already been successfully used for gas-phase analysis of TBAs, a novel N–As precursor ditertiarybutylaminoarsane and the corresponding P analogue ditertiarybutylaminophosphane. , …”
Section: Methodsmentioning
confidence: 99%